Glutamatergic medication in the treatment of obsessive compulsive disorder (OCD) and autism spectrum disorder (ASD) – study protocol for a randomised controlled trial. Issue 1 (December 2016) - Häge, Alexander; Banaschewski, Tobias; Buitelaar, Jan; Dijkhuizen, Rick; Franke, Barbara; Lythgoe, David; Mechler, Konstantin; Williams, Steven; Dittmann, Ralf
Abstract Background Compulsivity is a cross-disorder trait underlying phenotypically distinct psychiatric disorders that emerge in childhood or adolescence. Despite the effectiveness of serotonergic compounds in the treatment of obsessive-compulsive disorder, treatment-resistant symptoms remaining in 40 to 60 % of patients present a pressing clinical problem. There are currently no medications that effectively treat the core impairments of autism spectrum disorder. There is an urgent need for the development of conceptually novel pharmacological strategies. Agents targeting glutamate neurotransmission, such as memantine, represent promising candidates. This proof-of-concept clinical study will allow pilot-testing of memantine for both clinical effectiveness and tolerability/safety. Memantine is anN -methyl-D-aspartate receptor antagonist, approved for the treatment of Alzheimer's dementia in a number of countries. Methods/Design This 12-week study has an add-on, randomised, double-blind, placebo-controlled design of treatment with memantine, including an up-titration phase (forced flexible dose design, 5–15 mg/day), in patients aged 6–17 years and 9 months with obsessive-compulsive disorder or autism spectrum disorder. It is planned to include patients with obsessive-compulsive disorder (N = 50) or autism spectrum disorder (N = 50) across four centres in three European countries. Patients will be randomly assigned to memantine or placebo in a 1:1 ratio. Primary objectives are the investigation of the effectiveness of memantine in paediatric patients for improving symptoms of compulsivity (primary outcome measure: total score on the Children's Yale-Brown Obsessive-Compulsive Scale) and to explore its tolerability and safety. Secondary objectives are to explore the effects of memantine at the level of structure, function and biochemistry of the fronto-striatal circuits, and to collect blood for genetic analyses and biomarkers. Tertiary objectives are to explore the role of new candidate genes and pathways for compulsivity by linking genes to clinical phenotypes, response to treatment, neurocognitive test performance, and key structural and functional neuroimaging measures of the fronto-striatal circuits and to explore biomarkers/proteomics for compulsivity traits. Discussion This study is part of the large, translational project TACTICS (http://www.tactics-project.eu/ ) that is funded by the European Union and investigates the neural, genetic and molecular factors involved in the pathogenesis of compulsivity. Its results will provide clinically relevant solid information on potential new mechanisms and medication treatment in obsessive-compulsive and autism spectrum disorders. Trial registration EudraCT Number:2014-003080-38, date of registration: 14 July 2014.